Fine-needle aspiration cytology versus core needle lymph node biopsy in axillary staging of breast cancer - Omar M. Mahmoud; Mai El-MoatazBellah Khedrawy; Hasan Ibrahim Megally; Mahmoud Farouk Mohamed; Momtaz Thabet Allam (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Axillary lymph node status is an extremely important prognostic factor in evaluating and managing recently diagnosed breast cancer patients. So, preoperative evaluation of the lymph nodes in breast cancer patients with minimally invasive methods is of significant concern. Ultrasonography is the main modality used for this purpose, with advantages including the ability to help to guide the biopsy. This study aimed to compare ultrasound-guided fine-needle aspiration cytology (FNAC) and core needle biopsy (CNB) in their ability to detect metastatic disease in the axillary lymph nodes, as well as to estimate the accuracy of preoperative ultrasound-guided axillary lymph node biopsy for staging in patients with breast cancer. Results In total, 108 cases were included in the study, and 55.6% (60 cases) had metastases. The sensitivity for FNAC was 83.3%, and the specificity was 100%. The sensitivity for CNB was 100% and the specificity was 100%. The negative predictive value for FNAC was 81.5%, and that for CNB was 100%. The positive predictive value was 100% for both methods. Conclusions CNB biopsy shows higher sensitivity and accuracy than FNAC in the characterization of benign and malignant lymph nodes. FNAC is a suitable substitute when a smaller node is encountered, a node in an inaccessible site, or even an uncorrectable bleeding diathesis of the patient.